WIDAL: a secret language of Sundanese - Purnama, Agil (2014)
This research paper entitled "Widal: a secret language of Sundanese". Is aimed at providing a linguistic overview of Widal language, a Sundanese based secret language produced and developed by the people of Tipar, Sukabumi. This study employs the descriptive analysis to investigate the patterns in using Widal language. This research also uses morphology and phonology as tools in order to reveal the pattern of Widal language. The primary source of this study is the transcript of the recorded dialogue of Widal language users and some other Widal language words that used frequently by the people with Sundanese language as the reference. This study finds that Widal language is used randomly or no exact pattern in substitution of the letter as the result of the transformation from Sundanese to Widal. But on the other hand, the exact patterns are found in terms of particular affixation and particular usage of vowel in Widal language. Keywords: Secret language Widal language, Sundanese language.